Peran Gelandangan Dalam Revolusi Kemerdekaan Di Semarang (1945-1950) - Salawati, Annisa Rizki; Wibowo, Eka Yudha; Witasari, Nina (Journal of Indonesian History, 2025)
This study examines the role of homeless people in the Indonesian Independence Revolution in Semarang City in the period 1945–1950. The main focus of the study includes the socio-economic background of the emergence of homeless people, their contribution in the physical struggle against the Japanese and Dutch troops, and their involvement in struggle organizations such as Laskar Kere and Laskar Jembel. Using historical research methods—including heuristics, source criticism, interpretation, and historiography—this study highlights how homeless people, despite being socially marginalized, actively participated as fighters and spies in the struggle for independence. The study also reveals the passive side of some homeless people who remained mired in poverty and were not involved in the revolution. The findings show that homeless people have a complex role, both as active actors in the revolution and as symbols of the social impact of war and colonialism. This study enriches the understanding of urban social dynamics in the history of the nation's struggle.